2007
DOI: 10.1080/17453670610013529
|View full text |Cite
|
Sign up to set email alerts
|

The trochlea is medialized by total knee arthroplasty: An intraoperative assessment in 61 patients

Abstract: Our findings indicate that the trochlea is medialized by TKA. Because a conscious medialization of the femoral component in a TKA produces abnormal patellar tracking patterns, further investigations will be needed to analyze the clinical consequences of this medialization of the trochlea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 16 publications
1
26
0
1
Order By: Relevance
“…Thus, if such a component is positioned in the midline of a distal femur in which the native sulcus lies laterally, the prosthetic sulcus will be medialized with respect to the native sulcus. The prosthetic sulcus would then cause the patella to track laterally [5][6][7][8]11]. This in turn would lead to abnormal tracking patterns and higher stresses on the patella.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if such a component is positioned in the midline of a distal femur in which the native sulcus lies laterally, the prosthetic sulcus will be medialized with respect to the native sulcus. The prosthetic sulcus would then cause the patella to track laterally [5][6][7][8]11]. This in turn would lead to abnormal tracking patterns and higher stresses on the patella.…”
Section: Discussionmentioning
confidence: 99%
“…Mediolateral changes may result from a shift in the groove location due to one of several reasons: translation or axial rotation of the femoral component; changes in the soft-tissue tensions; or medialization or lateralization of the patellar component. Two recent studies have reported routine (i.e., unintended) medialization of the femoral groove due to arthroplasty [50,51]. Changes in spin were probably due to either the realignment of the leg as a result of the arthroplasty, or a change in the Q-angle based on the alignment of the components.…”
Section: Discussionmentioning
confidence: 99%
“…previous studies hypothesized that this high rate of patellofemoral complications might be linked to the medialization of the prosthetic femoral groove typical of this implant [24]. In a different study, Meijerink et al [25] noted a trend toward lateral tracking of the patella in early flexion when using the pFC Sigma prosthesis. Because of these issues, a new pFC Sigma pS System (De puy, Warsaw, USA) was introduced in 2009, with new instrumentation and a peculiar femoral design.…”
Section: Discussionmentioning
confidence: 94%